Never change - Berg, Elizabeth (New York Pocket Books, 2001)
Resigned to her life alone, fifty-one-year-old spinster Myra Lipinsky endures her isolation by immersing herself in her career as a visiting nurse, in which role she is reunited with Chip Reardon, the onetime golden boy she adored from afar in high school, who has returned to his New England hometown to live while he deals with an incurable illness.
78942
Keywords: Brain -- Tumors -- Patients -- Fiction; Middle aged women -- Fiction; Visiting nurses -- Fiction; Terminally ill -- Fiction; Single women -- Fiction; Psychological fiction